Employee Turnover and Company Value. Were European Companies Equally Affected by the COVID-19 Pandemic? - Garsaa, Aziza (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2024)
SummaryIn this study, we sought to identify how employee turnover affected company value in a sample of 254 European listed companies before and during the COVID-19 pandemic. We specifically tested the hypothesis that the most profitable and socially responsible companies withstood the pandemic better. We then complemented our analysis by identifying potential sectoral differences.We analyzed the association between employee turnover and company value by using a quantile regression model to determine this association at each point of the conditional distribution of company value. All of our financial and non-financial data for the 2019-2020 period were extracted from the Bloomberg database. We found a negative association between employee turnover and company value before and during the pandemic. The additional costs of employee turnover may have therefore reduced stock market values. The negative association weakened considerably during the pandemic for those companies that had the lowest company value, possibly because of the government support and guarantees they received during the lockdowns. Our sectoral analysis showed a stronger effect on traditional industries with intensive human interactions than on modern industries with predominantly virtual interactions. Estimation results from more profitable companies showed a positive association before the pandemic, perhaps because they had an ‘optimal’ level of employee turnover that maximized their productivity and performance and, thus, their stock market value. This association completely reversed during the pandemic, perhaps because their higher profitability was not sufficient to dampen the negative effect of the increase in employee turnover. For the most profitable and socially responsible companies, the same association was much stronger both before and during the pandemic. For almost all of the companies, the estimated coefficients of employee turnover were positive before the pandemic but became negative for those companies that had the lowest stock market values during the pandemic.This study enriches the existing literature by being the first one to show how employee turnover affected the company value of European listed firms before and during the pandemic. It also provides new evidence that this association varied with the level of sectoral sensitivity to the pandemic and was much stronger for the most profitable and socially responsible companies.